Abnormal dexamethasone suppression tests in a rifampicin-treated patient with suspected Cushing's syndrome - Ngow, Harris Abdullah; Nowalid, Wan Khairina Won Mohd (The Polish Society of Endocrinology, 2010)
The dexamethasone suppression test is a useful endocrinological test to diagnose Cushing's syndrome. However, its interpretation may be influenced by many factors such as stress, alcohol, failure to ingest the dexamethasone, altered metabolism, drug interaction and obesity. This report illustrates such an instance, whereby the result of the test was erratic due to the anti-tuberculous drug rifampicin. Rifampicin has been found to profoundly attenuate the biological effects of dexamethasone, probably by enhancing its metabolism in the liver. The exact mechanism of the drug interaction remains elusive, though induction of hepatic CYP3A4 enzyme complex is a possible mechanism. In a patient treated with rifampicin, the results of dexamethasone suppression tests thus have no diagnostic value and can be very misleading.